2015
DOI: 10.1155/2015/792041
|View full text |Cite
|
Sign up to set email alerts
|

Primary Breast Burkitt’s Lymphoma in an HIV-Infected Woman

Abstract: A 30-year-old HIV positive woman presented with a multifocal mass tumour associated with axillary and lateral-cervical lymphadenopathy in the right breast. Laboratory examination of the biopsy confirmed a case of mammary Burkitt's lymphoma with a nodular infiltration of the breast. Antiretroviral treatment and chemotherapy were effective to control the tumour. Although Burkitt's lymphoma rarely involves the breasts, it should be considered during routine breast examination of African woman.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…[ 6 14 ] Although pre-treatment CD4+ T cell levels and EBV status were not obtained due to the severity of presentation, the patient showed a good response to CHOP and antiretroviral therapy (ART), with shrinkage of the breast and axillary masses. A similar response to chemotherapy and ART was reported by Traoré et al [ 5 ]…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…[ 6 14 ] Although pre-treatment CD4+ T cell levels and EBV status were not obtained due to the severity of presentation, the patient showed a good response to CHOP and antiretroviral therapy (ART), with shrinkage of the breast and axillary masses. A similar response to chemotherapy and ART was reported by Traoré et al [ 5 ]…”
Section: Discussionsupporting
confidence: 86%
“…[ 3 ] The endemic form is almost always associated with a latent EBV (Ebstein-Barr Virus) infection and occurs mainly in sub-Saharan Africa; some authors have identified a residence in malaria-endemic regions as a risk factor. [ 4 5 ] Sporadic BL is not associated with EBV and occurs mostly in Caucasian populations. Lastly, immunodeficiency-related BL (IRBL) is seen in immunocompromised patients, the majority of which are HIV (Human Immunodeficiency Virus) positive or transplant recipients on immunosuppressive therapy.…”
Section: Introductionmentioning
confidence: 99%
“…3 In Africa, there is only 4 reported case of PBBL, 1 from Guinea in an HIV infected 30 years old woman, and 3 from Ivory Coast. 10,11 This case will represent the first case of PBBL from Uganda. Compared to other sites of extranodal NHL, it has been revealed that PBL tends to be more aggressive and has a much poor outcome 6 although this is disputed by some authors.…”
Section: Discussionmentioning
confidence: 98%